Measurable outcomes of consumer engagement in health research: A scoping review - DeBortoli, Emily; Soyer, H. Peter; Milne, David; Dissanayaka, Nadeeka; Gartner, Coral; Holt, Jeanette; Rae, Kym; Robison, Laura; Wallingford, Courtney K.; McInerney-Leo, Aideen M. (Frontiers in Public Health, 2022)
Background: Consumer engagement is increasingly recognised as an instrumental component of health research, with many institutions and international bodies mandating it as part of the research and funding process. Given an increasing utilisation of consumer engagement in health research, it is critical to identify the literature which support its value and tools that capture successful outcomes. To develop an overview of the literature, we conducted an umbrella scoping review exploring important outcomes of consumer engagement in health research combined with a scoping review of relevant frameworks. Specifically, we aimed to capture outcomes which reflect authentic and meaningful consumer engagement. Methods: Four databases (PubMed, Embase, CINAHL and Cochrane Library) were searched using key search terms. Records were included if they were review articles or frameworks that addressed outcomes of consumer engagement in health research. Data was analysed using descriptive statistics and an inductive qualitative content analysis. Identified outcomes were sorted based on the three most relevant stakeholder groups (consumer, researcher, institution). Results: A total of twenty articles that explored a variety of health disciplines were included. We identified fifteen measurable outcomes of consumer engagement in health research. Eight core outcomes were relevant to all stakeholder groups, and were considered fundamental to authentic consumer engagement including (1)trust, (2)empowerment, (3)respect, (4)confidence in the outcomes of the research, (5)transparency of the research process, (6)satisfaction with the consumer engagement program, (7)knowledge and experiences of consumers, and (8)degree of consumer engagement. Outcomes pertaining to specific stakeholder groups included representativeness and diversity of the consumer groups, research relevance to consumers, funding opportunities, quality/validity of the research, recruitment/retention rates, translation and dissemination of research, and interpretation of results. Conclusion: This review identified key measurable outcomes that could be captured when evaluating the impacts of consumer engagement on health research and the success of consumer engagement programs. All outcomes identified were relatively underexplored within the literature, and inadequately and/or inconsistently evaluated amongst studies. Future research should consult all stakeholder groups to identify outcomes perceived to be reflective of optimal consumer engagement.